If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 6 = 2y + -6 Reorder the terms: 6 + y = 2y + -6 Reorder the terms: 6 + y = -6 + 2y Solving 6 + y = -6 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 6 + y + -2y = -6 + 2y + -2y Combine like terms: y + -2y = -1y 6 + -1y = -6 + 2y + -2y Combine like terms: 2y + -2y = 0 6 + -1y = -6 + 0 6 + -1y = -6 Add '-6' to each side of the equation. 6 + -6 + -1y = -6 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = -6 + -6 -1y = -6 + -6 Combine like terms: -6 + -6 = -12 -1y = -12 Divide each side by '-1'. y = 12 Simplifying y = 12
| 5(v-8)=3v-38 | | 8(x+18)=5(x+78) | | x=0.001q | | 3+p=25 | | -18t+26=-19 | | 12-11z=-(-9z-4) | | 0=128x^3-776 | | h(x)=-x^2-6x | | 7x+3-9x=-13 | | -9a-4b=-56 | | -7+4(u+2)=22 | | (3*2-5)+(-2*2+3)= | | .5(2x+12)=.25(8x-16) | | y=2x^2+8x+6 | | -9a+4b=-16 | | -5+2m=-4m-2m-13 | | 8x^6+99x^3=125 | | 5(4x+9)=165 | | 0=8x^3+776 | | -12.5=-15.5q+4(3q-3) | | 1.5(4x-1.5)=.5x+14.25 | | 9-6(4n-1)=n+15 | | -2k+4(5-4k)=110 | | 0=48x^2+776 | | 3(2x+5)=5x+20 | | -0.4(5b-8)=0.08(10b-1) | | 19=6x-4x+9 | | -12-p=-22 | | -9=4x+x-9 | | 8(x-2)=16-8 | | (x+139)2=(x-5)11 | | x-2+8=3 |